Repair of Ceramic Ware in the Neolithic and Eneolithic (case study of the extreme North-East of Europe) - Viktor N. Karmanov (Археология евразийских степей)
The paper deals with the regional data on the repair of ceramic wares in the Neolithic and Eneolithic (VI–III millennia BC). Holes of various types at the edges of cracks on the broken pot or cracks that threatened its safety, as well as the remains of adhesive materials that sealed the repair seam, are evidence of ancient repairs of pots. As a result, it was determined that the oldest evidence of ware repair in the region is associated with early pottery (VI millennium BC). The need for pottery repair increases by the final Neolithic (second half of the IV millennium BC) and decreases in the Eneolithic (III millennium BC). The use of organic clamps and sealants is also uneven in diachrony. The use of adhesive materials is not revealed in Early Neolithic assemblages, on the contrary, it increases by the Final Neolithic, and in the Eneolithic it may be the only method of repair. Five samples of sealants from the Final Neolithic–Eneolithic Chuzhyael culture were analyzed by gas chromatography-mass spectrometry. It was found that the adhesive materials were tar obtained by the “double pot” method – heating the raw material in one pot while pouring the product into another container. The informative potential of the studied category of sources is determined by the complex of actions, tools and materials involved in pottery repair. Like any evidentially reconstructed artefact “biography”, pottery “history” can tell us about behavior of people and assess their needs and lifestyles.